Auditors’ comfort with uncertain estimates: More evidence is not always better - Rowe, Stephen P. (Accounting, Organizations and Society, 2019)
Prior research generally presumes that auditors assess better-supported management estimates as more reasonable. By contrast, I find that auditor’s reasonableness assessments regarding an estimate are not entirely based on the degree of management support, but are instead conditional on the level of estimate uncertainty. Drawing on information processing theory, I predict that auditors will assess an estimate as more reasonable when there is alignment between the degree of management support and the level of uncertainty versus when there is misalignment. I test this prediction using an experiment with experienced auditors and find that the level of uncertainty interacts with the degree of management support. Auditors assessed management’s estimate as less reasonable and expected a larger adjustment when management obtained less evidential support for an extremely uncertain estimate. More notably, however, auditors assessed management’s estimate as more reasonable and expected a lower adjustment when management obtained less evidential support for a moderately uncertain estimate. These findings demonstrate how natural triggers, such as misalignment between support and uncertainty, can decrease auditors’ reasonableness assessments of management estimates.